Vibrational communication and mating behavior of the greenhouse whitefly Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) - Fattoruso, Valeria (Sci Rep, 2021)
The greenhouse whitefly (GW), Trialeurodes vaporariorum is considered one of the most harmful insect pests in greenhouses worldwide. The GW mating behavior has been partially investigated and its vibrational communication is only in part known. A deeper knowledge of its intraspecific communication is required to evaluate the applicability of control methods based on techniques of behavioral manipulation. In this study, for the first time, we provided a detailed ethogram of the GW mating behavior and we characterized the vibrational signals emitted during the process of pair formation. We characterized two types of male vibrational emissions (“chirp” and “pulses”), differently arranged according to the behavioral stage to form stage-specific signals, and a previously undescribed Male Rivalry Signal. We recorded and characterized two new female signals: The Female Responding Signal and the Female Rejective Signal. The mating behavior of GW can be divided into six different stages that we named “call”, “alternated duet”, “courtship”, “overlapped duet”, “mating”, “failed mating attempt”. The analysis performed with the Markovian behavioral transition matrix showed that the “courtship” is the key stage in which male exhibits its quality and can lead to the “overlapped duet” stage. The latter is strictly associated to the female acceptance and therefore it plays a crucial role to achieve mating success. Based on our findings, we consider the use of vibrational playbacks interfering with GW mating communication a promising option for pest control in greenhouses. We discuss the possibility to start a research program of behavioral manipulation to control the populations of GW.